Analisis Implementasi Kebijakan SAP Berbasis Akrual Dinas Pendapatan, Pengelolaan Keuangan dan Aset (DPPKA) Pemerintah Kota Mojokerto - Ahmad Nasihuddin; Rachma Agustina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
Implementation of Accrual-Based Government Accounting Standards (SAP) can increase accountability and transparency and can produce comprehensive financial reports that can be measured properly. The purpose of this study was to find out and analyze how the implementation of the Akrul- based Government Accounting Standards policy in the Revenue, Financial Management and Regional Assets Office of Mojokerto City was measured using Edward theory, 4 factors of successful implementation, namely communication, resources, disposition / attitude of implementers and bureaucratic structure. The methode used in this research is descriptive qualitative research methode. The results showed that the implementation of the Accrual-based Government Accounting Standards policy in the Department of Revenue, Financial Management and Regional Assets of Mojokerto City was already good, but still needed a slight improvement in the area of appointment and selection of employees.